Effect of Dayak Onion (Eleutherine bulbosa (Mill.) Urb.) on the Immune Response and Gene Expression of Nile Tilapia (Oreochromis niloticus) Infected with Aeromonas hydrophila - Fauzi, Arini Resti; Yuhana, Munti; Widanarni, Widanarni; Setiawati, Mia; Afiff, Usamah (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Dayak onion (Eleutherine bulbosa (Mill.) Urb.) has the potential to be an immunostimulant to benefit fish health. This study aimed to evaluate the effectiveness of dietary supplementation with the powder and crude ethanol extracts of Dayak onion on the hematology and immune response parameters of Nile tilapia challenged with Aeromonas hydrophila. The research used a completely randomized design with six treatments and three replications. Nile tilapias were fed with Dayak onion (w/v) consisting of powders of 5% (P5), 10% (P10), and 15% (P15), while crude extract was 0.5% (E05) and given during rearing for 30 days. Positive control (C+) and negative control (C-) were used without Dayak onion. Nile tilapia in treatment C+, P5, P10, and P15 were injected with A. hydrophila 10â¶ CFU mLâ»1, while that in treatment C- was injected with phosphate buffered saline (PBS) intramuscularly. The results showed that the dietary with 15% powder and 0.5% crude extract significantly improved the hematology and immune response parameters compared to the control after the challenge against A. hydrophila (P<0.05). Dayak onion supplementation effectively increased the health status based on hematology and immune response parameters of Nile tilapia against A. hydrophila infection. Highlight Research Dayak onion has significant potential to improve nonspecific immunity in fish. Dayak onion improves hematology and immune response of Nile tilapia. Dayak onion can significantly regulate the immune system against A. hydrophila infection. Dayak onion significantly increases the production of the gene expression of IL-1β and TNF-α.